Reconstruction of Maxilla with Titanium Mesh and Fascia Lata - A Case Report - Rengaraja, Devkumar (J Clin Diagn Res, 2017)
Maxillary defect reconstruction has been a grave challenge which unfortunately has stopped many ENT surgeons from attempting maxillectomy due to the fear of reconstruction. With our technique of reconstructing the maxillary defect with titanium mesh and fascia lata, the need for microvascular assistance is obviated. Here we describe a revision case of ameloblastoma of maxilla in a 33-year-old female for which total maxillectomy with reconstruction was done without the aid of microvascular tissue transfer. The aim of this article is to encourage and alleviate the fear among the ENT surgeons, in attempting maxillectomy and its reconstruction for delivering an equally good aesthetic and functional outcome especially at the centres where the facility of plastic assistance is not readily available.